Regulating Control and Dynamics of the Migrant Population: International Practice - DANKO, Tamara Petrovna; ZAROVA, Elena Viktorovna; KISELEV, Vladimir Mihailovich; RAUSKIENE, Ona; SEIFULLAEVA, Maisa Emirovna; ZHURAVLEV, Pavel Viktorovich; GOROKHOVA, Anna Evgenyevna (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019DO - 10.14505//jarle.v10.2(40).09, 2020)
The research is an attempt to carry out marketing diagnostics of the development of migration flows in five rather developed countries of the world (Russia, the USA, Canada, Mexico, Argentina), and to make an analysis of their dependence on innovativeness. The migration of population is the resettlement of people from one region (state, country) to another, in some cases by large groups and over long distances. In her works O.D. Vorobyova, the Russian researcher, writes that the migration of population is ‘any territorial movement of the population associated with crossing both external and internal borders of administrative-territorial entities in order to change their permanent residence or temporary stay in the territory for study or work, regardless of the factors that have the prevailing impact – attracting or revolting’.